Nutrient and Food Intake of Indonesian Children Under 5 Years of Age: A Systematic Review. (January 2022) - Arini, Hesti Retno Budi; Hadju, Veni; Thomas, Preetha; Ferguson, Megan
The Indonesian Government's targets to reduce the prevalence of child malnutrition are unlikely to be met based on current progress. Adequate dietary intake is key to meeting these targets. This systematic review aimed to provide a comprehensive overview of the nutrient and food intake of Indonesian children under five years of age. Peer-reviewed and gray literature published between 2007 and 2019 were collected. Of 1500 records, 38 articles met the study inclusion criteria and a narrative analysis was conducted. Children under five years were reported to have ranging energy and macronutrient intakes, some with adequate protein intake. Micronutrient deficiencies, particularly iron, zinc, calcium, and vitamin C, were reported. Animal-source foods, fruits, and vegetables were consumed by children, but frequency and/or volume of consumption was low, and it is among the probable causes of micronutrient deficiency among children under five years. The absence of reporting micronutrient intake in the national survey limited evidence to inform nutrition-related policies. The implementation of a national micronutrient survey will be beneficial in informing policy and practice aimed at reducing the prevalence of child malnutrition in line with national targets, through improvement in dietary intake.